ANALISIS FAKTOREKONOMI DAN NON EKONOMI YANG MEMPENGARUHI TINGGI BADAN ANAK BALITA DI KECAMATAN SIPORA SELATAN KABUPATEN KEPULAUANMENTAWAI, 2011 - , Devi Novita ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study backs in the background by the high prevalence of children under five short (stunted) in the District of Sipora Selatan. The purpose of this study was to analyze the economic and non economic factors which influence the height of children under five in the District of Sipora Selatan in 2011. The data used in this study is the primary data by using cross-sectional study design, sample size 108 children, that is existing children under five in the District of Sipora Selatan in 6 villages. Samples were taken by sampling area, the data collection through interviews using a questionnaire. Analysis tools used in this study was the logistic regression analysis using Eviews program. Logistic regression analysis with Î± = 5%, was obtained that there is a positive and significant relationship between income families with a height of children under five (P=0,040) OR = 1.578, there is a positive and significant correlation between mother long education with a height of children under five (P=0,019) OR = 1.408, there is a negative effects and no significant association between mother employment status with a height of children under five (P=0,825), there is negative effects and no significant correlation between the number of family members with a height of children under five years (P=0,629), there is a positive effects and significant relationship between hygiene and environmental sanitation with a height of children under five (P = 0,017) OR = 1,080, and there is a positive and significant relationship between health parenting style with a height of children under five (P=0,002) OR = 1,080. Variation in the dependent variable (height of children under five) can be explained by the independent variable of 51,57 percent (McFadden R 2= 0,5157).